A Quality Initiative for Optimal Therapeutic Hypothermia during Transport for Neonates with Neonatal Encephalopathy. Issue 2 (March 2018) - Bourque, Stephanie L.; Meier, Stephanie A.; Palmer, Claire; Melara, Diane L.; Grover, Theresa R.; Delaney, Cassidy A.
Abstract : Introduction: Neuroprotection with therapeutic hypothermia (TH) is standard of care for neonatal encephalopathy (NE) and decreases death and neurodevelopmental disability. TH initiated shortly after birth insult results in greater neuroprotection compared with delayed initiation. Methods: Quality improvement methodology was used to improve temperature control during transport to a level IV neonatal intensive care unit. We included neonates with NE transported to a single institution for TH from 2010 to 2016. The quality improvement interventions were 2-fold. Review of the Transport Body Cooling Protocol revealed a suboptimal temperature goal of 34–35°C; this protocol was revised to 33–34°C. The second intervention was the implementation of an active cooling protocol. Clinical characteristics were compared using 2-sample t tests for continuous variables and Fisher's exact tests for categorical variables; statistical process control chart was used to monitor admission temperatures. Results: We obtained baseline data for 78 neonates admitted from 2010 to 2014. These data were compared with postintervention data for 26 patients admitted between 2015 and 2016. Distance transported, NE severity, and seizures were similar between the 2 groups. The use of active cooling increased from 8% preimplementation to 31% postimplementation ( P < 0.01). After implementation of the 2 interventions, more infants were admitted within the goal temperature of 33–34°C, 58% versus 22% ( P < 0.01), and the average neonatal intensive care unit admission temperature improved from 34.4 ± 0.8°C to 33.8 ± 0.8°C ( P < 0.01). Conclusion: Increased utilization of active cooling during transport for TH improves the percentage of neonates admitted within the target temperature range. However, 42% of neonates remained outside the target temperature range, supporting the need for additional tools to improve admission temperatures.